Spectrophotometric Determination of Lead in Tea Leaf Sample with Dibromo-p-chloro-arsenazo - Zhai, Qing-Zhou; Li, Jing-Mei; Zhang, Jun-Ping (Asian Journal of Chemistry, 2012)
This work reports the use of dibromo-p-chloro-arsenazo (DBC-ASA) as a chromogenic agent to develop a new spectrophotometric method for the determination of lead using Pb2+-(DBC-ASA) complex. In the medium of 0.10 mol L-1 phosphoric acid, the maximum absorption wavelength of Pb2+-(DBC-ASA) violet-red complex formed is located at 614 nm. At this wavelength a good linearity is presented between the concentration range of 0.1-3.5 μg mL-1 of lead(II) and absorbance and its linear regression equation is: A = 0.130 C (C:μg/mL) + 0.007. The apparent moler absorption coefficient of the method is 3.33 × 104 L mol-1 cm-1 and its detection limit is 0.225 μg mL-1. The method was used to determine lead in some tea leaf samples and the obtained results are in good agreement with those of atomic absorption spectrometry. The relative standard deviation of 13 replicate determinations was (0.43-0.80) %. The recovery of the standard addition of the method was (96.0-98.5) %.